ETHNOLINGUISTIC STUDY: AN ANALYSIS OF LINGUISTIC ASPECTS THROUGH MARRIAGE TRADITIONS OF SOUTHWEST ACEH - Rika Kustina; Nurul Fadila (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The traditional customs of marriage in the Southwest Aceh community are used by the traditional leaders during the implementation of customs. Implicitly, it represents the culture of the Southwest Aceh community. This uniqueness is rich in meaning that can be understood through teachings passed down by the traditional leaders. The purpose of this research is to analyze linguistic units and cultural meanings in the traditional customs of marriage in the Southwest Aceh community. This is a qualitative descriptive research with a theoretical and methodological research approach. The research data includes oral and written data, obtained from primary sources such as informants and secondary sources. Data analysis is done in three ways: data reduction, data presentation, and drawing conclusions. The research data shows that the linguistic aspects in the traditional customs of marriage in the Southwest Aceh community take the form of words, phrases, sentences, and discourses that can express cultural meanings reflecting the mindset and views of the Southwest Aceh community